ECOLOGICAL TERMINOLOGY AND TEXT TRANSLATION (KONFERENSIYA, 2025)
This article explores the formation of ecological terminology, its linguisticcharacteristics, origins, and the theoretical and practical challenges encountered intranslating ecological texts. Due to the rapid development of ecology as a science,new scientific terms emerge every year, and the expansion of international scientificcooperation makes the accurate translation of these terms essential. The articlescientifically analyzes the interdisciplinary nature of ecological terminology, itspolysemy, the critical role of context in translation, and the need to standardizeterminology used by international organizations. Furthermore, semantic distortions,stylistic inconsistencies, and methodological shortcomings frequently encountered inecological text translation are explained with examples. The study emphasizes thataccurate translation of ecological terms plays a crucial role in environmental policy,scientific research, ecological education, and the formation of environmentalawareness.